Academic library science and its contribution to the development of bibliology and information science in Poland, 1945–2015 - Jadwiga Konieczna (Roczniki Biblioteczne, 2024)
The aim of the study is to present the origins and development of academic institutions educat- ing librarians in Poland between 1945 and 2015, taking into account the institutional and scholarly aspects. In the first part of the paper the author presents the history of various institutions — university faculties, departments and institutes — arranged diachronically in three stages (1945–1974, 1975–1989, 1990–2015). She takes into account the circumstances of their establishment (including the legal framework), their organisers, staff, organisational structures and their changes. In addition, she points to other components of academic life influencing the work of academic library science centres, such as conferences and journals. In the second part, devoted to a discussion of bibliological and information-science research conducted at Polish universities, the author focuses on various issues, treating chronology only as an element organising descriptions of research processes at individual library studies centres. She identifies the areas of research, as well as changes in the thematic foci in the analysed period, citing selected scholars and their most important works. Like in part one, she also discusses the social, political and cultural determinants stimulating research processes, paying particular attention to the impact of new technologies and media. The author’s overview confirms the huge role the academic institutions engaged in library studies play in the consolidation of the position of bibliology as an academic discipline, but at the same time, she shows how the research profile of book studies has been changing in recent years, including issues associated with information science and new technologies.